Prosthetic management of partial anodontia with microdontia from 11 to 20 years of age - 10 years of follow up - Natarajan Kalavathy; Athimuthu Anantharaj; Nikhil Anantharaj; Harshita Mundhra; Bishakha Kanrar (Wolters Kluwer Medknow Publications, 2022)
Treatment of pediatric patients with partial anodontia is a challenge requiring interdisciplinary approach. Growth period, reduced vertical dimension, microdontia, and unacceptable esthetics present difficulties at various stages of prosthetic rehabilitation. Congenital absence of teeth impairs the nutritional status of the growing child and causes a psychological setback. This article describes the prosthetic management of a patient suffering from partial anodontia done over a period of 10 years. Considering the age and psychological and financial requirements of the patient, removable and fixed prostheses were fabricated at different phases of the treatment. The ultimate aim was restoration of function, improvement of esthetics, and overall psychological upliftment of the patient which was achieved by maxillary metal ceramic bridge and mandibular implant retained hybrid prosthesis.